Enhancing Democracy: Can Civic Engagement Foster Political Participation?. (4th November 2020) - Binder, Martin
Abstract : Objective: The aim of the present article is to address Tocqueville's hypothesis that voluntary associations and volunteering are breeding grounds for democratic virtues and skills and thus enhance political participation. Methods: Data from the British Household Panel Survey data set spanning the years 1991–2008 are analyzed using multivariate panel data regression techniques to assess the effect of voluntary association membership/activities on political participation in the United Kingdom. Results: It is found that organizational activity (more than mere membership) positively impacts political participation, but these effects are smaller than usually found and depend on types of associations and degree of activity. Sensitivity analyses support the finding that the political interest more strongly predicts political party support than associational activities. Further support for causal interpretations is scant. Conclusion: Some evidence for Tocqueville's hypothesis can be found for the United kingdom during the sample horizon, but the effect is sensitive to model specification and issues of reverse causation remain.